Development Of An Electrochemical Sensor Based On Molecularly Imprinted Go/Zno/Ppy Composites On Pencil Graphite Electrode For Determination Of Andrographolide - Hussain, Rabia Tasaduq (2021)
This research highlights the development of an electrochemical sensor based on graphene derivatives with a molecularly imprinted polypyyrole (PPy) layer on a pencil graphite electrode (PGE) to detect andrographolide, which is a bioactive component of an ancient plant known as Andrographis paniculata. Conventionally, andrographolide detection based on tedious and heavy instrumentation.